2021
DOI: 10.1177/01455613211051311
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Amyloid A Expression and Disease Control after Endoscopic Sinus Surgery in Patients With Chronic Rhinosinusitis With Nasal Polyps

Abstract: Objective Our previous study revealed that serum amyloid A (SAA) levels in polyp tissues could serve as a biomarker for the prediction of corticosteroid insensitivity in patients with chronic rhinosinusitis with nasal polyps (CRSwNP). However, their association with disease control status in the patients after endoscopic sinus surgery remains to be assessed. Methods Polyp tissues and control uncinate process mucosa were collected from 48 patients with CRSwNP and 10 healthy control subjects. SAA expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Based on the data of the current study, it is reasonable to assume that tissue neutrophils might have a protective role in favoring disease control in CRSwNP patients. Indeed, in our another study, we have shown that tissue serum amyloid A, a marker for neutrophilic inflammation, levels are associated with a better prognosis in patients with CRSwNP after surgery [36]. Further studies with large prospective cohorts are warranted to address these issues.…”
Section: Discussionmentioning
confidence: 80%
“…Based on the data of the current study, it is reasonable to assume that tissue neutrophils might have a protective role in favoring disease control in CRSwNP patients. Indeed, in our another study, we have shown that tissue serum amyloid A, a marker for neutrophilic inflammation, levels are associated with a better prognosis in patients with CRSwNP after surgery [36]. Further studies with large prospective cohorts are warranted to address these issues.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, Van der Veen et al (2017) found that the levels of control measured by EPOS2012 corresponded to mean total SNOT-22 and short form (36) health survey (SF-36) scores (p < 0.05). Lu et al (2021) found that increased serum amyloid A (SAA) level was associated with better disease control as measured by EPOS2012 criteria in patients with CRSwNP after ESS.…”
Section: Characteristics Of Different Disease Control Measuresmentioning
confidence: 99%
“…Five studies identified poor disease control in patients with CRS based on EPOS2012, and risk factors included tissue or blood eosinophilia, high CT score, bilateral disease, asthma, and allergic rhinitis. Furthermore, tissue eosinophil ratio >0.206, blood eosinophil ratio >0.025, Lund-Mackay score≥ 15, CT ethmoid score≥maxillary score, female gender, aspirin intolerance, and revision Functional endoscopic sinus surgery (FESS), low serum amyloid A (SAA) were independently associated with the poor disease control ( Van der Veen et al, 2017;Tao et al, 2018;Lu et al, 2021). Additionally, Wang et al (2019) found that concordant blood and tissue eosinophilia can predict poor control better than isolated blood or tissue eosinophilia.…”
Section: Predictors Of Poor Disease Control In Patients With Chronic ...mentioning
confidence: 99%
See 1 more Smart Citation